A critical evaluation of organizational readiness for continuous improvement within a UK public utility company. Issue 8 (17th November 2022) - Rodgers, Bryan; Anthony, Jiju; Cudney, Elizabeth A.
ABSTRACT: The purpose of the research reported here was to develop practical tools to assess organizational readiness prior to the implementation of a continuous improvement (CI) initiative in a public sector environment. A case study approach was used, which focused on a UK public utility company. The data was collected through a survey and the results were used to provide practical measures of readiness and inform the development of the initiative. The research synthesizes and builds on the existing literature in the areas of success, failure and readiness factors to develop a framework for the assessment of readiness for organizations undertaking CI initiatives.